Interleukin-1 receptor antagonist, a biomarker of response to anti-TB treatment in HIV/TB co-infected patients. Issue 5 (May 2017) - Nouhin, Janin; Pean, Polidy; Madec, Yoann; Chevalier, Mathieu F.; Didier, Celine; Borand, Laurence; Blanc, François-Xavier; Scott-Algara, Daniel; Laureillard, Didier; Weiss, Laurence
Summary: Objectives: Despite the high frequency of tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) in human immunodeficiency virus (HIV)/TB co-infected patients, no diagnostic test is available. Here, we investigated whether monocyte/macrophage activation markers can predict TB-IRIS occurrence and if they are modulated by anti-TB treatment. Methods: Frozen plasma was obtained from 127 HIV/TB co-infected adults naïve for antiretroviral therapy, enrolled in the CAMELIA trial, 36 of whom developed TB-IRIS. Concentrations of IL-1Ra, sCD14, and sCD163 were measured at anti-TB treatment onset (baseline), after 8 weeks of anti-TB treatment and at TB-IRIS time. Results: At baseline, IL-1Ra and sCD14 concentrations were similar in TB-IRIS and non-IRIS patients. sCD163 concentrations, although significantly higher in TB-IRIS patients, did not remain associated with TB-IRIS occurrence in multivariate analysis. At the time of TB-IRIS, patients displayed higher concentrations of IL-1Ra (p = 0.002) and sCD14 (p < 0.001). The most striking result was the significant decrease in IL-1Ra after 8 weeks of anti-TB treatment (median reduction: −63% (p < 0.0001)). Conclusions: None of the biomarkers tested was associated with TB-IRIS occurrence. However, repeated measurement of IL-1Ra could help for the diagnosis of TB-IRIS. The substantial reduction of IL-1Ra under treatment suggests that IL-1Ra could be a surrogate biomarker of anti-TB treatment response in HIV-infected patients. Highlights: None of the IL-1Ra, sCD14, and sCD163 biomarkers are associated with TB-IRIS. At IRIS event, IL-1Ra and sCD14 concentrations are higher in TB-IRIS patients. sCD14 concentrations remain stable under anti-TB therapy in HIV-infected patients. IL-1Ra concentrations significantly decrease within eight weeks of anti-TB therapy in HIV-infected patients.